Nyelvi kompetencia-elvárások a multikulturális munkaerő piacon - Feketéné Silye, Magdolna (Acta Agraria Debreceniensis, 2012)
Proficiency in a foreign language, especially when combined with knowledge of and skills in another professional area, is highly desirable in the multicultural marketplace. Just as business and media have experienced global changes over the last few decades, so, too, has grown the acceptence of English around the world as the lingua franca for economic and scientific exchange. Second language speakers increasingly turn to English as a requirement of international communication. It is more than understandable that in many European companies, proficiency in English may even be a hiring criterion (Inman, 1983). The spread of English thus privileges certain groups of people and may harm others who have less opportunity to learn it. One can rightly conclude that we are in an age when communicative language skills in English are an indispensible component of literacy. Many claim that this may well entail significant changes in the social and individual values of nations and people. This paper investigates some of those underlying social and economic processes that have over the past few decades brought English language literacy into the focus of the attention of many researchers and educators. In the framework of the paper, certain issues of the conceptual impact that these changes have (or are presumed to have) on English language education are also discussed.